Analisis Prosedur Pencairan Dana Langsung (LS) pada Kantor Pelayanan Perbendaharaan Negara (KPPN) Malang - Najlah Najlah; Adita Nafisa (CiDEA Journal, 2024)
Disbursement of funds is a stage carried out by the KPPN to provide funds to the entitled party or partner based on the Direct Payment Order (SPM-LS) issued by the Budget User Officer or Budget User Authorization, in accordance with valid evidence of expenditure. This process includes two main categories, namely employee expenses such as (salary, allowances, honorariums, and overtime) and non-employee expenses which include procurement of goods and services, as well as payment of utility costs such as (electricity, telephone, and air). This study aims to analyze the direct disbursement procedure at the Malang State Treasury Service Office. The technique used in this study is descriptive qualitative, where the data collected is analyzed to draw conclusions. The results of the study indicate that the direct disbursement procedure at the Malang KPPN is in accordance with the Regulation of the Minister of Finance Number 178 / PMK.05 / 2018 concerning Payment Procedures in the Framework of Implementing the State Revenue and Expenditure Budget.